English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-06 10:43:30 · 3 answers · asked by Eddy 2 in Science & Mathematics Mathematics

3 answers

i think u mean
sin 2x cos x- cos 2x sin x
=2 sin x cos x. cos x- (2 cos ^2 x -1) sin x
= 2 cos^2 x sin x- 2 cos^2 x sin x + sin x
= sin x

where sin 2x= 2 sin x cos x
cos 2x= 2 cos^2 x -1

2006-12-06 10:53:49 · answer #1 · answered by niel_alinda 3 · 1 0

Do you mean sin²(x) or sin(2x) ? Same question on the cosine term. It makes a difference ☺


Doug

2006-12-06 18:48:06 · answer #2 · answered by doug_donaghue 7 · 0 0

sin(2x)cos(x) - cos(2x)sin(x) = sin(x)

sin(2x) = 2sin(x)cos(x)
cos(2x) = cos(x)^2 - sin(x)^2

2sin(x)cos(x)cos(x) - (cos(x)^2 - sin(x)^2)sin(x) = sin(x)
2sin(x)cos(x)^2 - sin(x)cos(x)^2 + sin(x)^3 = sin(x)
sin(x)cos(x)^2 + sin(x)^3 = sin(x)
(sin(x))(cos(x)^2 + sin(x)^2) = sin(x)

cos(x)^2 + sin(x)^2 = 1

sin(x) = sin(x)

2006-12-06 20:17:29 · answer #3 · answered by Sherman81 6 · 0 0

fedest.com, questions and answers